2018
DOI: 10.3847/1538-3881/aaa75c
|View full text |Cite
|
Sign up to set email alerts
|

GTC/CanariCam Mid-IR Imaging of the Fullerene-rich Planetary Nebula IC 418: Searching for the Spatial Distribution of Fullerene-like Molecules

Abstract: We present seeing-limited narrow-band mid-IR GTC/CanariCam images of the spatially extended fullerenecontaining planetary nebula (PN) IC 418. The narrow-band images cover the C 60 fullerene band at 17.4 µm, the polycyclic aromatic hydrocarbon like (PAH-like) feature at 11.3 µm, the broad 9-13 µm feature, and their adjacent continua at 9.8 and 20.5 µm. We study the relative spatial distribution of these complex species, all detected in the Spitzer and Infrared Space Observatory (ISO) spectra of IC 418, with the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Observations of PN IC 418 also provide possible evidence for the proposed origin of C 60 . In this source, the 17.4 mm feature of C 60 and the 11.75 mm feature attributed to SiC dust grains were measured across the nebula (Díaz-Luis et al 2018). Note that the SiC feature varies from that seen in AGB stars, indicating some processing by the PN phase (García-Hernández 2012), and possibly acquiring a graphitic coating, consistent with our experiments.…”
Section: Resultssupporting
confidence: 85%
“…Observations of PN IC 418 also provide possible evidence for the proposed origin of C 60 . In this source, the 17.4 mm feature of C 60 and the 11.75 mm feature attributed to SiC dust grains were measured across the nebula (Díaz-Luis et al 2018). Note that the SiC feature varies from that seen in AGB stars, indicating some processing by the PN phase (García-Hernández 2012), and possibly acquiring a graphitic coating, consistent with our experiments.…”
Section: Resultssupporting
confidence: 85%
“…Fullerenes can form derivatives, such as partially hydrogenated fullerenes, which have also been suggested to be present in the interstellar matter (ISM; Stoldt et al 2001;Zhang et al 2017Zhang et al , 2020Díaz-Luis et al 2018). However, the additional hydrogens in such species destabilize the carbon cage due to the change in orbital hybridization from sp 2 to sp 3 (Van Lier et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly enough, the map presents some structure, even if this is not as marked as in e.g., NGC 7009 and NGC 3132, with higher extinction at the rim, where values can reach up to c(Hβ) = 0.33. In that sense, this pattern is more reminiscent of the ring-like structure detected in the bands associated to the PAH and C 60 than to the dust continuum emission at 9.8 µm [16].…”
Section: Reddeningmentioning
confidence: 84%
“…A previous IFS-based study on this nebula revealed a region of enhanced electron temperature by means of the [O III]4363/5007 line ratio, interpreted as a consequence of an inner photoionised shock caused by the stellar wind [15]. Mid-infrared maps in the 17.65-µm band (dominated by dust emission but containing a faint spectral feature due the C 60 fullerene), in the 11.3-µm band (containing dust emission and a spectral feature caused by polycyclic aromatic hydrocarbons, PAH), and the broad 9-13-µm feature display a ring-like structure while the dust continuum emission at 9.8 µm peaks closer to the central star [16]. Reported distances to the nebula range from 1.0 kpc [15] to 2.6 kpc [17].…”
Section: Introductionmentioning
confidence: 99%